Moral Development of Senior High School Students in Physics Learning Based on Traditional Game - Himawan Putranta (Postgraduate, University of Mataram, 2023)
Physics learning is carried out to develop students' cognitive, psychomotor, and morale. This phenomenological research aims to explore the moral development level of senior high school students in physics learning based on traditional games during Covid-19 pandemic. The research data were collected through in-depth interviews with eight physics teachers and eight senior high school students. The participants were selected using a purposive sampling technique. Data analysis uses analytic reduction which begins to identify important statements from interview results, determine core theme, and interpret interview results' essence. The research results found that physics learning in senior high schools during Covid-19 pandemic was integrated into traditional games. The student's moral development in physics learning-based on traditional games at second, third, fourth, and fifth levels. Moral development at the second, third, fourth and fifth levels sequentially is shown by the willingness to take part in physics lessons to move up grades, facilitate the application of physics concepts, explore abilities, and integrate physics learning into daily activities. It takes high-quality teachers and complete distance learning facilities so that students can optimize their moral development.